Overexpression of ctr1Δ300, a high‐affinity copper transporter with deletion of the cytosolic C‐terminus in Saccharomyces cerevisiae under excess copper, leads to disruption of transition metal homeostasis and transcriptional remodelling of cellular processes. Issue 5 (14th May 2013) - Schuller, Astrid; Auffermann, Gudrun; Zoschke, Katja; Schmidt, Ulrike; Ostermann, Kai; Rödel, Gerhard
Abstract: In an approach to generating Saccharomyces cerevisiae strains with increased intracellular copper amounts for technical applications, we overexpressed the copper transporter CTR1 and a variant of CTR1 with a truncation in the C‐terminus after the 300th amino acid ( ctr1Δ300 ). We determined the copper sensitivity of the generated strains and used inductively coupled plasma spectrometry analysis (ICP–OES and ICP–MS) to investigate the effects of overexpression of both constructs under excess copper on the cellular content of different elements in S . cerevisiae . In addition, we performed DNA microarray analysis to obtain the gene expression profile under the changed element contents. Overexpression of CTR1 increased the copper content in the cells to 160% and 78 genes were differentially regulated. Overexpression of the truncated ctr1Δ 300 resulted in an increased copper, iron and zinc content of > 200% and 980 genes showed differential expression. We found that transition metal ion homeostasis was disrupted in ctr1Δ300 ‐overexpressing strains under excess copper and that this was combined with a transcriptional remodelling of cellular processes. Copyright © 2013 John Wiley & Sons, Ltd.